Resource abundance, governance and economic performance in Turkmenistan and Uzbekistan - Richard Pomfret (University of Bonn, Center for Development Research (ZEF), 2004)
This paper analyses the connection between resource wealth, governance and economic performance in Turkmenistan and Uzbekistan. Since independence, both countries have remained heavily resource-dependent and they have had political stability, but despite some similarities, their economic situations have been diverging since the transition shock in 1991. Although the two countries are resource-abundant, their resource endowments differ: both have energy resources and farmland suited to cotton-growing, but Turkmenistan's resource base is heavily skewed towards natural gas, with cotton and oil of lesser importance, and with very little other economic activity. Uzbekistan's major exports are cotton and gold, with energy endowments sufficient to cover domestic needs but without substantial energy exports. Both oil fields and cotton fields yield rents and this paper estimates their scale and also examines how the different socio-economic linkages associated with each set of rents differentiates the capture of the rents and their deployment. The paper argues that during the first decade of transition the rents from both sets of natural resources could be realised with little recourse to FDI so that both regimes were able to resist pressure for rapid reform. However, despite acknowledged policy errors, Uzbekistan managed its rents more effectively and responsibly than Turkmenistan and it faces the more promising future.
Keywords: 320; International Development; Resource /Energy Economics and Policy; Rohstoffvorkommen; Rohstoffpolitik; Übergangswirtschaft; Rententheorie; Vergleich; Turkmenistan; Usbekistan